Correlation of Sun Exposure Score and Vitamin D Intake withSerum 25(OH)D Levels in Older Women - Husna, Kholidatul; Widajanti, Novira; Sumarmi, Sri; Firdaus, Hadiq (UI Scholars Hub, 2021)
Introduction. Indonesia is a tropical country, but the prevalence of vitamin D deficiency in older women is high due to the lack of sun exposure and low vitamin D intake. Some previous studies have reported that people from rural areas have higher serum 25(OH)D levels compared to those from urban areas. This study was conducted to analyze the correlation between sun exposure score and vitamin D intake with serum 25(OH)D levels of older women from rural areas. Methods. This was an analytic cross-sectional study involving older women in two villages from Wonorejo and Kraton Districts, Pasuruan Regency, in June 2020 during the dry season. The sun exposure score was calculated using a sun exposure questionnaire, vitamin D intake was obtained using the 2 x 24-h food recall, and serum 25(OH)D levels were measured using the chemiluminescent immunoassay. The data was analyzed using the Spearman and Pearson correlation test. Results. A total of 40 post-menopausal women aged 60 to 93 years (median age 70 years) were included in this study. The median sun exposure score was 14. The median time spent outdoors was 40 minutes, 90% of subjects wore longsleeved and long skirts, and all of the subjects never put on sunscreen. The mean value of vitamin D intake was 1.73 μg/day (SD 3.21 μg/day), all of the subjects had low vitamin D intake. The primary source of their vitamin D intake was fish (67.5%), predominantly freshwater fish. The mean value of serum 25(OH)D levels was 27.75 ng/mL (SD 13.25 ng/mL), and 30% of them had vitamin D deficiency. The sun exposure score was positively correlated with serum 25(OH)D levels (r=0.425; p=0.006). Meanwhile, there was a correlation between vitamin D intake and serum 25(OH)D levels (p=0.246). Conclusion. There is a significant positive correlation between sun exposure score and serum 25(OH)D levels, but no correlation between vitamin D intake and serum 25(OH)D levels.